SPATIO-TEMPORAL ANALYSIS OF THE HUMMOCK DISTRIBUTION TO IDENTIFY THE CHANGE OF CONSTRUCTION MATERIALS POTENCY AT JEMBER AREA, EAST JAVA - Djihad, Fajar
The southeastern region of East Java, Indonesia, named Jember Regency is known as the city of “a thousand hummock”. The hummock is composed of volcanic product material (sand as matrix and stone as fragment) has been widely mined by the local communities as a construction materials. The objective of this study is to map the distribution of volcanic products during 2000 to 2020 using ASTER satellite imagery to analyze their change based on spatio-temporal observation. So that within a period of about twenty years, it can be analyzed the change of hummock distribution due to the mining activities by local communities. In 2000 there were 480 hummocks that were successfully delineated using DEM SRTM data with a total area of 1274 Ha. In 2008 the area of the hummock was reduced to be 1245 Ha due to mining activities in 27 locations. The location of mined hummock increased to be 53 locations in 2016, causing the remained area of hummock decreased to be 1220 Ha. In 2020 there are 1183 Ha of hummock area and there were 65 locations of hummock have been mined during about last 20 years. Petrographic observation and XRF (X-Ray Fluorescence) analysis performed on 13 igneous rock samples from different hummocks showed the igneous rock types of basalt, trachybasal, basaltic andesite, basaltic trachyandesite, andesite, and dacite. Based on the material composition and fragment size, the hummock consists of three types, namely block facies, matrix facies and mixed facies. The anisotropy direction based on the variogram model of hummock area distribution showed the largest continuity in northeast-southwest direction with range about 2100 to 3900 m.